Faktor-Faktor yang Mempengaruhi Happiness at Works pada Karyawan di Sektor Pendidikan di Jakarta - Aziz, Muhammad Abdul; Berliyanti, Dita Oki (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the impact of Organizational Justice, Emotional Wage, and Workplace Social Courage on Happiness at Work among teachers in public high schools in Jakarta. The sample used in this study consists of 296 teachers randomly selected from various high schools. The method employed in this research is regression analysis to test the relationships between variables AMOS and SPSS version 25. The results indicate that Organizational Justice has a significant positive effect on both Emotional Wage and Happiness at Work, as well as on Workplace Social Courage. However, the effects of Emotional Wage and Workplace Social Courage on Happiness at Work were not found to be significanteffect which is processed using. The implications for educational management highlight the importance of creating a fair work environment to enhance teachers' well-being, which in turn contributes to the quality of education.